"Family policy": How do we define it? - Séraphin, Gilles; St-Amour, Nathalie (Enfances, Familles, Générations, 2020)
Research Framework : This article is part of a broader reflection on the future of family policies, including their beneficiaries, the change of levels responsible for their development and implementation, and the delegitimization of intermediary bodies involved in this process. Objectives : To better define the parameters of family policies and to outline the elements of a frame of reference that could be used to map the scope of this policy area in different countries. Methodology : This article is based on the contributions in this thematic issue, a review of the literature, and the research expertise of the authors. Results : The ideas presented in this article focus on delimiting the scope of family policies by analyzing the beneficiaries, the intervention fields, the founding principle(s) and the actors. Based on the cases of France and Quebec, the authors present, in the form of questions, the criteria that could make it possible to define how family policy is defined in a given region. Conclusions : At international and often at national levels, the scope of family policy still appears vague. In fact, it is impossible to provide a single and shared definition, adapted to all the countries where the term is used. Despite some commonalities, "family policy" remains difficult to define. Contribution : The authors confirm that family policies cannot be understood without being considered in the context of the current dynamic of the social state as a whole.